Situation Report: Romania, 1 March 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Second Congress of National Union of Agricultural Production Co-Operatives Ceausescu to Visit Africa in March Macovescu in Bonn Conflict of Generations Evident in Recent Reshuffles on Literary Reviews Drama Section of Writers' Union Meets Romania Fails to Join Two Comecon Associations Coverage of Nixon's Visit to China Yugoslav Military Delegation Visits Romania Sihanouk to Romania? Relations with EEC